Technologic peculiarities of large-scale orthophotogrammetric mapping in urbanised territories - Sužiedelytė-Visockienė, Jūratė; Žalnierukas, Albinas (Geodesy and Cartography, 2012)
Technologic peculiarities of large-scale 1:1000(or 1:2000) orthophotomaps creation in urbanized territories are described. Orthophotogrammetric processing is described and analysed, parameters of accuracy presented. Practical recommendation are given. Influence of cartographic projection is studied. Aerial photo is recommended as colour analogue or digital. For orthophotomapping of scale 1:1000 is recommended 1:5000 scale aerial photo and for 1:2000 scale is recommended 1:8000 scale aerial photo. The suggested size or aerial colour photonegative (diapositive) smallest scanning element (pixel) is 15 μm. Aerial triangulation networks could be established by digital automatic method. Suitability or terrain model is computed from formulas (6) and (7). For joining raster aero images into mosaic it is important to take into consideration perspectives of large buildings, separating fragments by middle lap line. The smallest element of orthophoto map is pixel 10 μm. Clear lines of map RMS error in relation to geodetic reference is designed up to 0,40 mm(marginal errors are double).Article in Lithuanian.Urbanizuotų teritorijų kartografavimo ypač stambiu masteliu ortofotogrametrinės technologijos ypatumaiSantrauka. Aprašomos urbanizuotų teritorijų ypač stambaus mastelio (1:1000–1:2000) spalvotų ortofotografinių žemėlapių sukūrimo, taikant naujausias technologijas, galimybės. Pateikiami technologijos ypatumai ir tikslumo duomenys, rekomenduojami aerofotonuotraukos sudarymo parametrai. Aptariami aerofotonuotraukų skenavimo darbai, pateikiamas tinkamiausias vaizdo elemento (pikselio) dydis, skenavimo geometrinis tikslumas, nurodomi aerotrianguliacijos variantai, skaitmeninio reljefo modelio sudarymo žingsnio dydis bei tikslumas, analizuojami ortofotografinio žemėlapio generavimo ypatumai. Raktažodžiai: ortofotogrametrinis kartografavimas, aerotrianguliacija, skaitmeninis reljefo modelis.First published online: 03 Aug 2012